Artemis Fowl - Book 1 - Colfer, Eoin (New York : Disney Hyperion, 2001)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.
Keywords: Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Fairies -- Juvenile fiction; Kidnapping -- Juvenile fiction; Magic -- Juvenile fiction; Mothers and sons -- Juvenile fiction; England -- Fiction; England -- Juvenile fiction; Juvenile fiction